Molecular Diversity of Microbes Associated with Fermented Bamboo Shoots - Vijay Kumar; Bindu Naik; Sachin Sharma; Akhilesh Kumar; Javed Masood Khan; Mohammad Irfan (Tropical Life Sciences Research, 2022)
Fermented bamboo shoots are rich in high protein, carbohydrates, fibre and minerals while low in fat content. In the North-East region of India and other Asian countries, they are mostly used in various food preparations. The present study was undertaken to explore the diversity of bacteria associated with Bamboo shoots and to evaluate their antibacterial profile. Based on the results the fermented bamboo shoots showed viable counts ranging from 6.55 ± 0.91 log CFU/g to 7.86 ± 1.21 log CFU/g. The 16s rRNA sequence analysis showed that these isolates belonged to the genus Bacillus (Bacillus safensis, B. tequilensis, B. siamensis, B. nakamurai, B. subtilis) and Enterobacter. These isolates have not been reported previously from fermented bamboo shoots except B. subtilis. Surprisingly, no Lactobacillus species or molds were found in any of the samples tested. Potent antibacterial activity was recorded against Klebsiella, Staphylococcus aureus, Salmonella and B. cereus.